Size-effect of Kondo scattering in point contacts (revisited): Электpонные свойства металлов и сплавов - Yanson, I. K.; Fisun, V. V.; Bobrov, N. L.; Mydosh, J. A.; Ruitenbeek, J. M. van (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The size-effect of Kondo-scattering in nanometer-sized metallic point contacts is measured with the simplified, mechanically-controlled break-junction technique for CuMn alloy of different Mn concentrations: 0.017; 0.035; and 0.18 (± 0.017) at.%. The results are compared with our previous publication on nominally 0.1 at.% CuMn alloy [1,2]. The increase of width of the Kondo resonance and enhanced ratio of Kondo-peak intensity to electron-phonon scattering intensity is observed for contacts with sizes smaller than 10 nm. From the comparison of electron-phonon scattering intensity for the pressure-type contacts, which correspond to the clean orifice model, we conclude that the size effect is observed in clean contacts with the shape of a channel (nanowire).